Broad spectrum efficacy with LY2969822, an oral prodrug of metabotropic glutamate 2/3 receptor agonist LY2934747, in rodent pain models. (13th March 2017) - Johnson, Michael P; Muhlhauser, Mark A; Nisenbaum, Eric S; Simmons, Rosa M A; Forster, Beth M; Knopp, Kelly L; Yang, Lijuan; Morrow, Denise; Li, Dominic L; Kennedy, Jeffrey D; Swanson, Steven; Monn, James A
Abstract : Background and Purpose: A body of evidence suggests activation of metabotropic glutamate 2/3 (mGlu2/3 ) receptors would be an effective analgesic in chronic pain conditions. Thus, the analgesic properties of a novel mGlu2/3 receptor agonist prodrug were investigated. Experimental Approach: After oral absorption, the prodrug LY2969822 rapidly converts to the brain penetrant, potent and subtype‐selective mGlu2/3 receptor agonist LY2934747. Behavioural assessments of allodynia, hyperalgesia and nocifensive behaviours were determined in preclinical pain models after administration of LY2969822 0.3–10 mg·kg −1 . In addition, the ability of i.v. LY2934747 to modulate dorsal horn spinal cord wide dynamic range (WDR) neurons in spinal nerve ligated (SNL) rats was assessed. Key Results: Following treatment with LY2934747, the spontaneous activity and electrically‐evoked wind‐up of WDR neurons in rats that had undergone spinal nerve ligation and developed mechanical allodynia were suppressed. In a model of sensitization, orally administered LY2969822 prevented the nociceptive behaviours induced by an intraplantar injection of formalin. The on‐target nature of this effect was confirmed by blockade with an mGlu2/3 receptor antagonist. LY2969822 prevented capsaicin‐induced tactile hypersensitivity, reversed the SNL‐induced tactile hypersensitivity and reversed complete Freund's adjuvant – induced mechanical hyperalgesia. The mGlu2/3 receptor agonist prodrug demonstrated efficacy in visceral pain models, including a colorectal distension model and partially prevented the nocifensive behaviours in the mouse acetic acid writhing model. Conclusions and implications: Following oral administration of the prodrug LY2969822, the mGlu2/3 receptor agonist LY2934747 was formed and this attenuated pain behaviours across a broad range of preclinical pain models.